Dynamic tightness evaluation of salt cavern energy storage. (January 2023) - Wei, Xinxing; Shi, Xilin; Hu, Wei; Ban, Shengnan; Li, Yinping; Ma, Hongling; Li, Peng; Yang, Chunhe
Abstract: Salt cavern tightness evaluation is a prerequisite for salt cavern energy storage. The current salt cavern tightness testing method can only qualitatively evaluate the salt cavern tightness. In this paper, using logging data from a 61-day closed well in a salt cavern of the Jianghan gas storage cavern, a classification model is developed to analyze the factors affecting salt cavern tightness. A hierarchical model is established to analyze the influence weights of temperature and pressure on salt cavern tightness. A population competition model is constructed to analyze the relative importance of pressure and temperature in evaluating salt cavern tightness. Combined with the results of the above analysis, a principal component analysis evaluation model of salt cavern tightness at different moments is established. The accuracy of the evaluation model is verified by combining pressure data. Then, a prediction model is established to analyze the late changes in pressure. The results of the models show that the pressure change has the greatest influence on the salt cavern tightness. The possibility of salt cavern tightness destabilization increases in the pressure anomaly region. The established dynamic evaluation method of salt cavern tightness has a reference value for the engineering practice. Highlights: A classification model is established to analyze the influence factors of salt cavern tightness. A hierarchical analysis model is established to analyze the effect of temperature and pressure on salt cavern tightness. A population competition model is established to analyze the effect of temperature and pressure on salt cavern tightness. An evaluation model is established to analyze the real-time dynamic tightness of salt caverns. An engineering evaluation method for salt cavern tightness is established.